Analysis of the Implementation of the Online Mortgage Registration System - Sri Budi Purwaningsih; Melinda Nur Artanti (Athena: Journal of Social, Culture and Society, 2025)
The encumbrance of collateral for land rights or so-called Mortgage Rights is carried out by registration at the Land Office in accordance with Law Number 4 of 1996. But this has been replaced by the regulation of the Minister of Agrarian Affairs and Spatial Planning of the National Land Agency Number. 5 of 2020 which transfers the process of registering mortgage rights to electronic. Registration that was originally carried out by PPAT is now switched to involve the creditor. With the legislative normative method, this research aims to find out whether the integrated system is sufficient to be applied simultaneously for electronic mortgage rights services. What if an error occurs when inputting the electronic mortgage document. The results of this study indicate that HT-el registration is more efficient in terms of time but there is still a need for supervision regarding the reading of electronic documents if the server experiences interference.